2017
DOI: 10.14500/aro.10150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sarcocystis Species (Sarcocystis ovicanis and Sarcocystis capricanis) in Tongue Muscle of Sheep and Goats in Duhok Province, Kurdistan Region, North Iraq

Abstract: Abstract-Sarcocystis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…It seems useful to do accurate recognition of S. hirsuta and S. hominis thick-walled cyst but it was not possible for us considering some problems in ultrastructure observation of primary cysts wall via electron microscopy which is too expensive and difficult to access (30). In present histopathological investigation, opposite to some studies which reported the existence of inflammatory reactions around some sarcocysts continuing to degeneration (18,21,29), no inflammatory reaction was found.…”
Section: Discussioncontrasting
confidence: 61%
“…It seems useful to do accurate recognition of S. hirsuta and S. hominis thick-walled cyst but it was not possible for us considering some problems in ultrastructure observation of primary cysts wall via electron microscopy which is too expensive and difficult to access (30). In present histopathological investigation, opposite to some studies which reported the existence of inflammatory reactions around some sarcocysts continuing to degeneration (18,21,29), no inflammatory reaction was found.…”
Section: Discussioncontrasting
confidence: 61%
“…Estimation of the coccidian protozoa prevalence (cyst either bradyzoite) form by using various approach including Macroscopy (detection of Macro-cyst) Microscopy (Pepsin /Trypsin digestion, impression on slide or squash squeezing smear and histopathology approach), Serology either by ELISA or IFA and also molecular approach is recently wildly used for detection of the gene prevalent (Bahari et al 2014;Metwally et al 2014;Meistro et al 2015;Banothu et al 2017;Zangana and Hussein 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our study findings show a significant difference between the different methods applied for identification of Sarcocystis spp. Hydrochloric acid digestion method used as a great measurement for any organ associated with presence of the microcyst development stage and it gives high accuracy rate up to 100% with presence of the bradyzoites featured in banana shape and the nucleus appeared towards to the posterior end when stained by H &E and toluidine blue and considered as a gold standard method by many researchers (Arshad et al 2007;Zangana and Hussein 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Latif et al (1999) Whaeeb et al (2016) in Baghdad studied the molecular structure of four Sarcocystis species from sheep esophagus and muscle. Zangana and Hussein (2017) in Duhok Province, Kurdistan region, Northern Iraq studied the prevalence of S. ovicanis and S. capricanis in sheep and goats tongue muscle. Scioscia et al (2017) reported three S. fusiformis.…”
Section: Introductionmentioning
confidence: 99%